Prospective and retrospective study of incisional hernias in a tertiary care hospital - C. P., Harikrishnan; Vakayil, Happy Johny (International Surgery Journal, 2017)
Background: Incisional hernias are the most common complications of laparotomy. The aim of the present study was to assess and analyse the risk factors leading to development of incisional hernia, different modalities of treatment adopted, postoperative complications and surgical outcome in these patients on follow up. Methods: This was a combined prospective and retrospective study conducted on 100 cases of incisional hernia admitted to the Department of Surgery, Jubilee Mission Medical College Thrissur, Kerala during the period 2013 - 2015. The technique of the repair was decided by the size of the hernial defect, abdominal muscle tone and general condition of the patient. Postoperatively patients were followed up for detection of possible complications and their treatment. Results: Majority of the patients were in the age group of 41-50 years. Female preponderance was observed. Postpartum sterilisation in about 30 cases tops the list of prior operation predisposing to incisional hernia. Pain and swelling was the most common complaint noted in 70 cases. The major risk factor noted was cough in about 60% cases. Elective surgeries were done in 85cases and emergency surgeries in 15 cases. Nausea was the immediate complication observed in about 25 cases. Pain and induration was the major late complication observed in 60 cases. Conclusions: Incisional hernias are more common among females. Cough following previous surgery was the most important risk factor followed by wound infection. Among the repair techniques, complications were lesser and recurrence least for those repaired by mesh, darning and transverse double breasting (Mayo’s).